Effect of bias voltage and carrier gas on the hydrogen gas-sensing properties of tungsten oxide nanobeads - Hoa, Nguyen Duc; Dang, Ngoc Son; Dang, Thi Thanh Le; Nguyen, Thi Thu Hoa; Chu, Manh Hung; Nguyen, Van Duy (Communications in Physics, 2021)
We investigated the effect of bias voltage and carrier gas on the hydrogen sensing performance of tungsten oxide nanobeads. The tungsten oxide nanobeads were prepared by a template-assisted method followed by calcination. The porous single walled carbon nanotube thin film was used as sacrificed template for the deposition of tungsten, followed by thermal calcination at high temperature to oxidize W into WO3 and to burn out the template. The crystal structures and morphology of the synthesized materials were characterized by X-ray diffraction, field-emission scanning electron microscopy, high-resolution transmission electron microscopy and Raman spectra. Hydrogen gas sensing properties were tested in air and in N2 as refence for comparison.  Our results indicated that Schottky junction was formed at the interface of WO3 and Pt electrodes. The sensor operated under revered bias voltage processed excellent hydrogen sensing performance. In addition, the H2 sensing performance of the WO3 nanobeads is higher when measured in N2 gas as reference.